Expression of E2 gene of CSFV and analysis of epitope diversity - Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Abdul Rahman, Sheikh Omar; Bahaman, Abdul Rani; Ideris, Aini; Mutalib, Abdul Rahim (Veterinary Association Malaysia, 2009)
Infection of cells with Classical Swine Fever Virus (CSFV) is mediated by the interaction of envelope glycoproteins with receptor molecules on the cell surface. The E2 protein is one of the major envelope antigens for eliciting neutralising, antibodies, conferring protective immunity. The study found a distinct substitution of two amino acids at positions 94 (R→G) and 97 (P→S) in the deduced E2 protein sequence of GPE strain of CSFY, which contributed to O.5% difference from the original sequence. Nevertheless, successful E2 expression from the plasmid cassette was determined via in vitro. Two-different MAbs, WH303 and WH211, were used for E2 protein detection. The E2 detection was accomplished by using MAb WH211. However; the usage of the MAb WH303 for the E2 expression analyses was unsuccessful. It was observed that the alanine in minimal antigenic domain recognised by WH303 had been substituted with tyrosine in the critical epitope of E2 peptide of GPE- strain at position 163. Therefore, the mapping data for these neutralising epitopes will be useful for the development of diagnostic tests.